GAL4 transcription factor is not a "zinc finger" but forms a Zn(II)2Cys6 binuclear cluster. - Pan, T (1990)
The DNA-binding domain of the transcription factor GAL4, consisting of the 62 N-terminal residues and denoted GAL4(62*), contains a Cys-Xaa2-Cys-Xaa6-Cys-Xaa6-Cys-Xaa2-Cys-Xaa6+ ++-Cys motif, which has been shown previously to bind two Zn(II) or Cd(II) ions. Binding of Zn(II) or Cd(II) is essential for the recognition by GAL4 of the specific palindromic DNA sequence to which it binds upstream of genes for galactose-metabolizing enzymes, the UASG sequence. On the basis of the 113Cd NMR chemical shifts of the two bound 113Cd(II) ions, we propose a binuclear cluster model for this Zn(II)-binding subdomain. 1H-113Cd heteronuclear multiple-quantum NMR spectroscopy and phase-sensitive double-quantum filtered 1H correlation spectroscopy of the 112Cd(II)- and 113Cd(II)-substituted GAL4(62*) derivatives provide direct evidence that the two bound 113Cd(II) ions are coordinated only by the six cysteine residues, two of which form bridging ligands between the two 113Cd(II) ions. The latter can be identified from the pattern of 1H-113Cd J coupling. Thus a binuclear metal ion cluster rather than a "zinc finger" is formed by the six cysteine residues of the GAL4 DNA-binding domain. This model can be directly applied to eight other fungal transcription factors which have been shown to contain similarly spaced Cys6 clusters. 1H NMR spectra of apo-GAL4(62*) suggest conformational fluctuation of the metal-binding subdomain upon removal of Zn(II) or Cd(II). Both Cd(II)2- and Zn(II)2-containing species of GAL4 can be formed, and the similar 1H NMR spectra suggest similar conformations.